DESIGN OF DATA COLLECTION SYSTEM OF LECTURER’S RESEARCH AT INSTITUTE INFORMATICS AND BUSINESS DARMAJAYA LAMPUNG - Sutedi Sutedi; Melda Agarina (IJISCS (International Journal of Information System and Computer Science), 2018)
In order to spur the quantity and quality of research is one of the basic tasks of the lecturer, Institute Informatics and Business Darmajaya Lampung facilitate the professors to be able to participate in a range of grants to help financing research lecturer.  With a growing number of studies professors proposed then it should be when logging the lecturer research done in a better. Utilization of information technology is the right information to perform data management information can be either information related to it or also as tool of checking data in order to reduce plagiarism practices and publishing redundancy title research